Slovenia’s trade with Pacific Rim countries, notably Australia - Romih, Dejan (LeXonomica, 2021)
Slovenia is dependent on trade with the rest of the world, especially with the rest of Europe, its most important foreign buying and selling market. European countries account for 90% of the value of Slovenia’s trade with the rest of the world. There are several reasons for this, such as the relatively short distance between Slovenia and other European countries. If Slovenia wants to increase the value of its trade with non-European countries, it should adopt a number of measures such as increasing the effectiveness and efficiency of its trade promotion. In this paper, the author discusses opportunities for increasing the value of Slovenia’s trade with Pacific Rim countries, notably Australia. Slovenska trgovina z državami tihooceanskega loka, zlasti z Avstralijo. Slovenija je odvisna od trgovine z ostalim svetom, zlasti z ostalo Evropo, ki je njen najpomembnejši tuji nabavni in prodajni trg. Trgovina z evropskimi državami predstavlja 90 % vrednosti slovenske trgovine z ostalim svetom. Za to obstaja nekaj razlogov, kot je relativno kratka razdalja med Slovenijo in drugimi evropskimi državami. Če želi Slovenija povečati vrednost njene trgovine z neevropskimi državami, mora sprejeti številne ukrepe, kot je povečanje učinkovitosti njene trgovinske promocije. V tem članku avtor razpravljata o možnostih za povečanje vrednosti slovenske trgovine z državami tihooceanskega loka, zlasti z Avstralijo.